Nutrition BMI and Dysmenorrhea in Adolescent Girls at Lembata's Senior High School 1: A Cross-Sectional Study - Talahatu, Anna Henny; Bewa, Maria Magdalena Ina; Boeky, Daniela LA (Pergizi Pangan DPD NTT, 2025)
Background: Dysmenorrhea, which refers to painful menstrual periods, is a widespread gynecological issue that affects teenage girls and may influence their academic achievements and overall quality of life. Objective: This research sought to explore the relationship between dietary habits, body mass index (BMI), and the occurrence of painful menstrual periods among teenage girls at Senior High School. Methods: A quantitative, cross-sectional approach was employed. The research involved female students between the ages of 15 and 18, who were chosen using stratified random sampling methods. Information regarding nutritional intake was gathered through a validated food frequency questionnaire (FFQ), and BMI was determined using the recorded height and weight measurements. Results: Energy intake had no relationship with the incidence of dysmenorrhea, while protein and fe intake were found to be associated with the incidence of dysmenorrhea. (the p-value of protein is 0.006 OR=0.237 and the p-value of fe is 0.004=OR=0.252). BMI has a relationship with the incidence of dysmenorrhea with a p-value = 0.014 OR= 0.811. The research concludes that insufficient nutrition and unusual BMI are strongly linked to the prevalence of dysmenorrhea in adolescent females. Conclusions: Encouraging a balanced diet and maintaining a healthy body weight may assist in lowering the risk and effects of dysmenorrhea in teenagers.